Impact of Grade I obesity on respiratory mechanics during video laparoscopic surgery: prospective longitudinal study - Araujo,Orlandira Costa (2020)
Abstract Introduction and objectives: The association pneumoperitoneum and obesity in video laparoscopy can contribute to pulmonary complications, but has not been well defined in specific groups of obese individuals. We assessed the effects of pneumoperitoneum in respiratory mechanics in Grade I obese compared to non-obese. Methods: Prospective study including 20 patients submitted to video laparoscopic cholecystectomy, normal spirometry, divided into non-obese (BMI ≤ 25 kg.m-2) and obese (BMI > 30 kg.mg-2), excluding Grade II and III obese. We measured pulmonary ventilation mechanics data before pneumoperitoneum (baseline), and five, fifteen and thirty minutes after peritoneal insufflation, and fifteen minutes after disinflation (final). Results: Mean BMI of non-obese was 22.72 ± 1.43 kg.m-2 and of the obese 31.78 ± 1.09 kg.m-2, p < 0.01. Duration of anesthesia and of peritoneal insufflation was similar between groups. Baseline pulmonary compliance (Crs) of the obese (38.3 ± 8.3 mL.cm H2O-1) was lower than of the non-obese (47.4 ± 5.7 mL.cm H2O-1), p = 0.01. After insufflation, Crs decreased in both groups and remained even lower in the obese at all moments assessed (GLM p < 0.01). Respiratory system peak pressure and plateau pressure were higher in the obese, albeit variations were similar at moments analyzed (GLM p > 0.05). The same occurred with elastic pressure, higher in the obese at all times (GLM p = 0.04), and resistive pressure showed differences in variations between groups during pneumoperitoneum (GLM p = 0,05). Conclusions: Grade I obese presented more changes in pulmonary mechanics than the non-obese during video laparoscopies and the fact requires mechanical ventilation-related care.